Vận dụng hằng đẳng thức chứng minh biểu thức 2x-x^2-1<0 với mọi số thực x luôn dương

Vận dụng hằng đẳng thức chứng minh biểu thức 2x-x^2-1<0 với mọi số thực x luôn dương

1 bình luận về “Vận dụng hằng đẳng thức chứng minh biểu thức 2x-x^2-1<0 với mọi số thực x luôn dương”

  1. Giải đáp:
     ta có:
    2x-x^{2}-1
    =-(x^{2}-2x+1)
    =-(x^{2}-2.x.1+1^{2})
    =-(x-1)^{2}
    Ta có:
    (x-1)^{2}\ge0∀x\inRR
    => -(x-1)^{2}<0∀x\inRR(đpcm)
    Vậy 2x-x^{2}-1<0∀x\inRR
     

    Trả lời

Viết một bình luận

Câu hỏi mới